Perceptual and motor performances between fencers and non-fencers - Akpinar, S.; Beyaz, O. (SportMont, 2018)
Sports participation can improve many cognitive and physical performances. It is important to test different sports in diff erent perceptual and motor tests in order to expose the demands of sports. Thus, in this study, we investigated if there are some perceptual and motor performance diff erences between fencers and aged match sedentary group. Nineteen fencers and nineteen non-fencers performed choice reaction time in an aiming task. Reaction time (RT), accuracy, and velocity of the movements were measured. Result displayed that fencers had signifi cantly faster RT, better accuracy with faster movements compared to non-fencers. These fi ndings suggest that participating a sport requiring fast and accurate pointing movements can modify perceptual and motor performance parameters. Thus, it could be better to select participants who have better perceptual and motor performances. Moreover, speed-accuracy trade off proposed by Fitts (1954) can be altered through long-term sport participation.